RESTORATIVE JUSTICE BETWEEN CHILDREN AS VIOLATORS AND CHILDREN AS VICTIMS IN THE CHILD CRIMINAL JUSTICE SYSTEM IN INDONESIA - Putu Sekarwangi Saraswati (Faculty of Law, Universitas Pekalongan, 2025)
Children are very valuable assets for a nation, this makes the State must pursue various policies to protect the growth and development of the children themselves. One of the efforts made is to provide maximum protection to children in conflict with the law. Related to children who have problems with the law both as perpetrators and as victims, of course law enforcement officials should provide special space for children in criminal justice related to the punishment of children and the conditions of children who are victims so that children's rights are protected. Efforts to protect the rights of children in conflict with the law, then the settlement of cases against children in conflict with the law and as victims, of course, the settlement requires all elements of both children being perpetrators, children being victims, law enforcement officials, and the community to realize a court based on the protection of children. Justice based on the protection of children in conflict with the law and as victims is one of them by using the principle of restorative justice. Keywords: Children, Juvenile Criminal Justice, Children's Interests, Restorative Justice